Diagnostic yield and appropriate indication of upper endoscopy in Jordanian children - Eyad Altamimi; Yousef Odeh; Tuka Al-quraan; Elmi Mohamed; Naif Rawabdeh (BMC, 2021)
Abstract Background Upper endoscopy is an essential tool for diagnosing pediatric gastrointestinal issues. This study aimed to assess the indications, diagnostic yields, concordance between histopathological and endoscopic findings and suitability of upper endoscopies performed at a tertiary university hospital in Jordan. Methods Hospital records of children who underwent upper endoscopy were retrospectively reviewed. Demographics, endoscopic details (e.g., indications, findings and any complications), and histopathological findings were collected. The relationship between endoscopic findings and histopathological abnormalities was reported. Results The study included 778 patients (age, 92.5 ± 54.5 months; 380 girls, 48.8%). The most common age group was children younger than 60 months (273 patients, 34.3%). The most common indication for endoscopy was abdominal pain, followed by vomiting and failure to thrive or weight loss. Normal upper endoscopy was reported in 411 patients (52.8%). Age below 60 months, abdominal pain, dysphagia/odynophagia, and heartburn were predictive of abnormal endoscopy in multivariate analysis with p-value 0.000, 0.048, 0.001 and 0.01 respectively. Abnormal endoscopy showed 67.3% sensitivity and 69.9% specificity to predict histopathological abnormalities. Of those performed, 13.6% endoscopies were described as inappropriate indication. The suitability of the procedure was a sensitive predictor for abnormal endoscopic and histopathological findings. Conclusions Abdominal pain is the most common indication for upper endoscopy in our population. It is associated with a higher chance of abnormal endoscopy. Concordance between endoscopic and histopathological findings is not high. Normal endoscopic findings shouldn`t discourage the endoscopist from obtaining tissue biopsies. Considering more biopsies may improve pathological detection rates. Compliance with established endoscopy guidelines may reduce unnecessary procedures.